Gli aggettivi con prefisso un- nel lessico di Notker III di San Gallo - Carla Riviello (Filologia Germanica, 2024)
ADJECTIVES WITH THE ‘UN-’ PREFIX IN THE VOCABULARY OF NOTKER III OF SAINT GALL. Notker’s ‘translations’ are conceptual and cultural – as well as linguistic, of course –, thus they required a highly precise vocabulary capable of representing with clarity the  semantic richness of the Latin text. It is therefore not surprising to note the sheer number of nouns, adjectives, and verbs used once or more times here that are not to be found anywhere else in Old High German. This paper aims to focus on adjectives formed with prefix un-, which make up an interesting corpus. A brief description of the corpus will also be provided, in order to enlighten the derivational and compositional processes by which these adjectives are formed. Finally, the attention will be focused on specific translation strategies. The analysis of selected examples will make it possible to identify which instruments in the German Wortbildung guided Notker’s refined sensibility, allowing him time after time to find pertinent and appropriate solutions in Old High German.